2018
DOI: 10.1002/sctm.18-0009
|View full text |Cite
|
Sign up to set email alerts
|

Secretome of Undifferentiated Neural Progenitor Cells Induces Histological and Motor Improvements in a Rat Model of Parkinson's Disease

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative movement disorder that results from the death of dopamine (DA) neurons. Over recent years, differentiated or undifferentiated neural stem cells (NSCs) transplantation has been widely used as a means of cell replacement therapy. However, compelling evidence has brought attention to the array of bioactive molecules produced by stem cells, defined as secretome. As described in the literature, other cell populations have a high‐neurotrophic activity, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 75 publications
9
52
0
Order By: Relevance
“…Although no straightforwardly matching data are available from the literature, the obtained results can be indirectly compared with other studies. For instance, the obtained NPC secretory pro les show 71% overlap with the results of Mendes-Pinheiro et al (2018), who applied proteomic approach to the primary cultures of human neuronal progenitors and identi ed 538 secreted proteins [43]. Signi cant overlaps of the obtained GPC secretory pro les with the corresponding data for primary cultures of human astrocytes should be noted as well [44][45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 50%
“…Although no straightforwardly matching data are available from the literature, the obtained results can be indirectly compared with other studies. For instance, the obtained NPC secretory pro les show 71% overlap with the results of Mendes-Pinheiro et al (2018), who applied proteomic approach to the primary cultures of human neuronal progenitors and identi ed 538 secreted proteins [43]. Signi cant overlaps of the obtained GPC secretory pro les with the corresponding data for primary cultures of human astrocytes should be noted as well [44][45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 50%
“…Though the disconnect between in vitro and in vivo gene expression may at first suggest that only in vivo studies should be pursued, such a focused approach does not faithfully represent all biologically and therapeutically relevant stem cell sources. Current clinical trials use cultured neural stem cell lines while preclinical models use NSPCs with varying amounts of in vitro processing (Mazzini et al 2019;Ottoboni, Merlini, and Martino 2017;Mendes-Pinheiro et al 2018;Chandanala et al 2014). Thus, analysis of both cultured and acutely isolated stem cells is critical for the development of effective NSPC-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells’ secretome, the collection of growth factors, cytokines, microvesicles, and other components, has only recently come under more thorough investigation as a means of further understanding the mechanisms by which stem cells can be used to manage disease. In a study published in Stem Cells Translational Medicine , Mendes‐Pinheiro et al used conditioned media (CM) from human neural progenitor cells (hNPC) in a rat model of Parkinson's disease (PD) to observe the effects of the cells’ secretome compared with treatment with undifferentiated hNPC . They found significant improvement in the density of thymidine hydroxylase‐positive cells in the brains of PD rats treated with hNPC CM, potentially explaining improvement in motor deficits they observed in the rats.…”
Section: Related Publicationsmentioning
confidence: 99%
“…Greater understanding of the transcriptomic and epigenetic basis for how a cell may respond to specific stimuli is essential for development of optimized cellular therapies. In a related article, Mendes‐Pinheiro et al evaluated the secretome of human neural progenitor cells to identify specific therapeutic proteins involved in tissue healing in a rat model of Parkinson's disease . These cell‐ and tissue‐specific insights add to a growing awareness of factors that contribute to variation from study to study and can provide clues for greater understanding of differences observed among patients in clinical settings.…”
mentioning
confidence: 99%